Maria Robaszkiewicz / Tobias Matzner (eds.): Hannah Arendt. Challenges of Plurality, Springer 2021.: Hannah Arendt: Challenges of Plurality. - Livingstone, Joshua (HannahArendt.net, 2023)
Hannah Arendt: Challenges of Plurality, edited by Maria Robaszkiewicz and Tobias Matzner, is a wonderful collection of essays on a central topic of Hannah Arendt’s political theory—plurality. It appears at a time of growing interest in Arendt. And with this growing interest there is growing need for the elucidation and critique of the key concepts that enrich Arendt’s writing and inform her unique account of politics. The volume delivers on both clarificatory and critical fronts.